2013
DOI: 10.1111/jawr.12123
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating the Effects of Landscape Development on Streams in Urbanizing Watersheds

Abstract: This collaborative study examined urbanization and impacts on area streams while using the best available sediment and erosion control (S&EC) practices in developing watersheds in Maryland, United States. During conversion of the agricultural and forested watersheds to urban land use, land surface topography was graded and vegetation was removed creating a high potential for sediment generation and release during storm events. The currently best available S&EC facilities were used during the development proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 50 publications
(88 reference statements)
0
29
0
1
Order By: Relevance
“…Available results varied heavily but were consistently higher than those found here: Pelacani et al (2008) et al (2015) estimated erosion in the MagdalenaEslava sub-basin in Mexico City at 'less than' 5000 Mg km -2 year -1 , presenting this as a low value relative to expectation. Such a large scale difference from the current study is presumably the result of differences in the physical geography of the basin (the authors describe the Magdalena-Eslava sub-basin as possessing steep slopes and fast currents, while rivers in the Milton Keynes/Bedford/Luton area are relatively small) as well as significant differences in climate, land management, and construction practices (Hogan et al 2014). While available published values are considerably higher than those modelled here, differences in climate, land cover, soil properties and management practices, coupled with uncertainties in the nature and modelling of urban soil erosion, confound valid comparisons.…”
Section: Sediment Deliverymentioning
confidence: 55%
“…Available results varied heavily but were consistently higher than those found here: Pelacani et al (2008) et al (2015) estimated erosion in the MagdalenaEslava sub-basin in Mexico City at 'less than' 5000 Mg km -2 year -1 , presenting this as a low value relative to expectation. Such a large scale difference from the current study is presumably the result of differences in the physical geography of the basin (the authors describe the Magdalena-Eslava sub-basin as possessing steep slopes and fast currents, while rivers in the Milton Keynes/Bedford/Luton area are relatively small) as well as significant differences in climate, land management, and construction practices (Hogan et al 2014). While available published values are considerably higher than those modelled here, differences in climate, land cover, soil properties and management practices, coupled with uncertainties in the nature and modelling of urban soil erosion, confound valid comparisons.…”
Section: Sediment Deliverymentioning
confidence: 55%
“…The U.S. Geological Survey (USGS), U.S. Environmental Protection Agency (US EPA), and Montgomery County Department of Environmental Protection (MC DEP) have monitored conditions in four study watersheds since 2004, providing over 14 years of high‐frequency (5‐minute interval) streamflow and precipitation measurements. Previous work in these watersheds has focused on analysis of aggregated flow metrics on the order of daily, monthly, or annual changes in streamflow (Bhaskar, Hogan, & Archfield, ; Hogan, Jarnagin, Loperfido, & Van Ness, ; Loperfido, Noe, Jarnagin, & Hogan, ) rather than sub‐daily changes in streamflow characteristics from individual storm events. These more aggregated metrics indicated that smaller flow events are better controlled by distributed SCMs than centralized SCMs (Loperfido et al, ), and that baseflow increased post‐development with distributed SCMs with combined loss of evapotranspiration and infiltration of stormwater (Bhaskar et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…This stream gage was installed in July 2004, and therefore, we use the period 1 October 2004–30 September 2014 for analysis. Tributary 104 is a recently urbanized watershed that was converted from agricultural and forested land to primarily suburban neighbourhoods between 2002 and 2010 (Figure ) (Hogan et al , ). During urbanization, vegetated land cover declined from 95% in 2002 to 68% in 2012, and impervious surfaces increased to 30% during that same time (Figure ).…”
Section: Introductionmentioning
confidence: 99%